2017
DOI: 10.1167/iovs.16-20569
|View full text |Cite
|
Sign up to set email alerts
|

ANRIL: A Regulator of VEGF in Diabetic Retinopathy

Abstract: Our results demonstrate for the first time that ANRIL regulates VEGF expression and function in diabetic retinopathy. This regulation is mediated by p300, miR200b, and EZH2 of the PRC2 complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 68 publications
(87 reference statements)
8
161
0
Order By: Relevance
“…McArthur et al demonstrated that ANRIL regulated the expression of VEGF through recruiting PRC2 or p300 and regulating the expression of miR‐200b in a rat model of diabetes mellitus . Thomas et al found that ANRIL upregulated the expression of VEGF through interaction with P300, PRC2 or miR‐200b, which resulted in vascular endothelial injury …”
Section: Resultsmentioning
confidence: 99%
“…McArthur et al demonstrated that ANRIL regulated the expression of VEGF through recruiting PRC2 or p300 and regulating the expression of miR‐200b in a rat model of diabetes mellitus . Thomas et al found that ANRIL upregulated the expression of VEGF through interaction with P300, PRC2 or miR‐200b, which resulted in vascular endothelial injury …”
Section: Resultsmentioning
confidence: 99%
“…Guo, Hu, Hu, He, & Li, 2018), differentiation (Gao, Ge, Li, Zhou, & Xu, 2018), and chromosome inactivation (Yue & Ogawa, 2018 (Hu, Jiang, & Jiang, 2017). Besides, the importance of lncRNA ANRIL in other diseases, like atherosclerosis (Chi et al, 2017) and diabetic retinopathy (Thomas, Feng, & Chakrabarti, 2017), have also been gradually reported. In the current study, we found that the expression of lncRNA ANRIL was significantly elevated in response…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al demonstrated for the first time that antisense noncoding RNA (ANRIL) regulates vascular endothelial growth factor (VEGF) expression and function in diabetic retinopathy. This regulation is mediated by p300, miR200b, and EZH2 of the PRC2 complex . Arnes et al indicated that β‐cell long intergenic noncoding RNA 1 (βlinc1), a conserved lncRNA, is necessary for the specification and function of insulin‐producing β cells through the coordinated regulation of a number of islet‐specific transcription factors located in the genomic vicinity of βlinc1 .…”
Section: The Possible Mechanism Of Lncrna In Dcmmentioning
confidence: 99%
“…This regulation is mediated by p300, miR200b, and EZH2 of the PRC2 complex. 86 Arnes et al indicated that β-cell long intergenic noncoding RNA 1 (βlinc1), a conserved lncRNA, is necessary for the specification and function of insulin-producing β cells through the coordinated regulation of a number of islet-specific transcription factors located in the genomic vicinity of βlinc1. 74 Reddy et al suggested that lncRNA E330013P06 (E33) can serve as novel therapeutic targets to attenuate inflammation and atherogenic potential of macrophages and concomitant diabetes complications.…”
Section: Lncrnas Associate With Dysfunction Of Islet β Cellmentioning
confidence: 99%
See 1 more Smart Citation